Business Model: Economic Value and Sociocultural Impact - G. D. Paksiutov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article examines the reasons for Netflix's economic success. It is noted that Netflix's growing popularity is an example of the processes of digitization and globalization characteristic of modern cultural industries. Among the main reasons for Netflix's economic success are an effective automatic system of recommendations and a high degree of vertical integration – a combination of the service of all stages of the film business: from the decision to produce content to its display to final consumer. The impact of Netflix on the practice of consuming films in the digital age has been considered, noting that the automatic system of recommendations used by the service and algorithms of search optimization can pose a threat to the free choice of consumers. Netflix's success is seen in terms of the West's unsymmetrical influence on global culture. The author concludes that Netflix's model is an example of the growing commercialization of cultural industries, the commodification of culture and carries certain risks of an aesthetic and cultural nature. However, it shows economic feasibility. For minimization of the related sociocultural risks it is important to keep alive a variety of forms of cultural production and consumption – a task in which the state can play a significant role.